Tucumã oil (Astrocaryum vulgare) ameliorates hepatic antioxidant defense system in alloxan-induced diabetic mice - Baldissera M.D. (2018)
© 2017 Wiley Periodicals, Inc.The aim of this study was to investigate whether treatment with Astrocaryum vulgare oil (tucumã oil), a hypoglycemic natural compound, was able to reduce hepatic oxidative stress of diabetic mice. An increase in lipid peroxidation and decrease in catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), and glutathione S-transferase (GST) activities, as well as glutathione reductase (GSH) levels were observed in diabetic/water group. Treatment with tucumã oil prevented lipid peroxidation and inhibition of CAT and SOD activities in diabetic mice. The tucumã oil treatment may provide effective protection against lipid oxidative damage in the liver tissue of diabetic mice, since it improved the enzymatic antioxidant defense system. Therefore, the tucumã oil can be an important coadjutant in the treatment of diabetes, contributing to the prevention and reduction of oxidative damage. Practical applications: Recently, it was demonstrated that tucumã oil exerts potent antihyperglycemic effect in alloxan-induced diabetic mice. The oil improved the pancreatic oxidant/antioxidant status, playing an essential role in the hypoglycemic effect. The results showed that tucumã oil can reduce oxidative stress in liver tissue, and consequently, prevent the hepatic alterations caused by high glucose levels.